Values in the Supreme Court : decisions, division, and diversity - Cahill-O'Callaghan, Rachel (Chicago : Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book draws on theories and techniques from psychology to understand the role of values in Supreme Court decision making. It centres on a novel method of content analysis of judgments to reveal the values that underpin decision making and discusses the potential implications this may have for developments in the law and the appointment of the judiciary. The book examines those cases which divide judicial opinion, Dworkin's hard cases "in which the result is not clearly dictated by statute or precedent". In hard cases there is real uncertainty about the legal rules that should be applied and factors beyond the traditional legal sources may influence the decision making. It is in these uncertain cases, where legal developments can rest on a single judicial decision, that values are revealed in the judgments"--
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: United States. -- Supreme Court -- Decision making; Judicial process -- United States; Political questions and judicial power -- United States; Constitutional & administrative law; Electronic books